2004
DOI: 10.1080/02791072.2004.10399720
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Substance Use, Mental Health, and Criminal Justice Involvement of Adolescents at Treatment Entry and at Three, Six, 12 and 30 Month Follow-Up

Abstract: Many adolescents entering substance abuse treatment have coexisting mental health problems and are criminally involved. Examination of the complexities of substance use, mental health, and criminal justice involvement along with changes in these issues following treatment is needed. This study includes 941 males and 266 females enrolled in seven drug treatment programs located in geographically diverse areas of the United States. Comparisons between males and females at treatment entry and three, six, 12 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 13 publications
4
40
0
1
Order By: Relevance
“…A total of 1207 adolescents entering substance abuse treatment programs were observed for 30 months in one study [33]. The trajectory of change and response to treatment were similar for both sexes over time.…”
Section: Treatment Responsementioning
confidence: 97%
See 4 more Smart Citations
“…A total of 1207 adolescents entering substance abuse treatment programs were observed for 30 months in one study [33]. The trajectory of change and response to treatment were similar for both sexes over time.…”
Section: Treatment Responsementioning
confidence: 97%
“…Adolescent boys entered therapeutic community drug treatment programs due to legal mandate and criminal justice system involvement signifi cantly more than girls [33,40]. One study reported that 5 years after treatment initiation, males were more likely to have exhibited violent behaviors such as drug traffi cking, but females were more likely to have had drug involvement and victimization [40].…”
Section: Course Of Illnessmentioning
confidence: 98%
See 3 more Smart Citations